Comparison of Vaginal and Plasma Fibronectin Concentrations for Prognosis of Preterm Delivery: A Cross-Sectional Study - Mohammad Hassan Meshkibaf; Zahra Moradi; Saeedeh Jafarzadeh; Azizallah Dehghan; Ameneh Keshavarzi (Fasa University of Medical Sciences, 2023)
Background & Objective: Prediction of preterm delivery can reduce a large number of its complications. The present study aimed to compare vaginal and plasma fibronectin concentrations in the diagnosis of preterm delivery. Materials & Methods: Serum samples were obtained from 105 women at 24-36 weeks of gestation. However, only 40 women gave permission to collect vaginal samples. Fibronectin concentration was measured using the ELISA technique. Then, plasma and vaginal fibronectin levels were compared in term and preterm deliveries. Results: The mean plasma fibronectin level was 6226.43±7174.97 ng/ml among the mothers with term infants and 7724.01±1143.82 ng/ml among those with preterm infants (p=0.667). The mean fetal fibronectin level was 156.61±126.42 ng/ml among the mothers with term infants and 127.71±43.14 ng/ml among those with preterm infants (p=0.241). The cut-off point of plasma fibronectin level was 1750 ng/ml with a sensitivity of 80.25% and specificity of 85.17%. Additionally, the cut-off point of vaginal fibronectin level was 158.98 ng/ml with a sensitivity of 94.62% and specificity of 22.08%. Conclusion: Plasma fibronectin analysis had lower sensitivity and higher specificity compared to vaginal fibronectin analysis. This implies that plasma testing has lower false-positive cases and can identify a more significant number of true positive cases of preterm delivery.